Cross-Species Application of Illumina iScan Microarrays for Cost-Effective, High-Throughput SNP Discovery - Fountain, Emily D.; Zhou, Li-Chen; Karklus, Alyssa; Liu, Qun-Xiu; Meyers, James; Fontanilla, Ian K. C.; Rafael, Emmanuel Francisco; Yu, Jian-Yi; Zhang, Qiong; Zhu, Xiang-Lei; Pei, En-Le; Yuan, Yao-Hua; et al. (Frontiers in Ecology and Evolution, 2021)
Microarrays can be a cost-effective alternative to high-throughput sequencing for discovering novel single-nucleotide polymorphisms (SNPs). Illumina’s iScan platform dominates the market, but their commercial microarray products are designed for model organisms. Further, the platform outputs data in a proprietary format. This cannot be easily converted to human-readable genotypes or be merged with pre-existing data. To address this, we present and validate a novel pipeline to facilitate data analysis from cross-species application of Illumina microarrays. This facilitates the generation of a compatible VCF from iScan data and the merging of this with a second VCF comprising genotypes derived from other samples and sources. Our pipeline includes a custom script, iScanVCFMerge (presented as a Python package), which we validate using iScan data from three great ape genera. We conclude that cross-species application of microarrays can be a rapid, cost-effective approach for SNP discovery in non-model organisms. Our pipeline surmounts the common challenges of integrating iScan genotypes with pre-existing data.